2017
DOI: 10.2134/jeq2016.08.0286
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Reduction of Estrone to 17β‐Estradiol by Rhizobium, Sphingopyxis, and Pseudomonas Isolates from the Las Vegas Wash

Abstract: Environmental endocrine-disrupting compounds (EDCs) are a growing concern as studies reveal their persistence and detrimental effects on wildlife. Microorganisms are known to affect the transformation of steroid EDCs; however, the diversity of estrogen-degrading microorganisms and the range of transformations they mediate remain relatively little studied. In mesocosms, low concentrations of added estrone (E1) and 17β-estradiol (E2) were removed by indigenous microorganisms from Las Vegas Wash water within 2 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, the formation of E2β in the present study may be due to the possibility of introducing intermittent anoxic conditions in the mesocosms when adjusting their soil moisture levels during incubation. Previous studies have reported the reduction of E1 to E2β in environmental matrices such as soil columns (Goeppert et al, 2015;Du et al, 2021), suspended swine manure under anerobic conditions (Prater et al, 2015), and inoculated water under anerobic conditions (Blunt et al, 2017). In Du et al, (2021) the reduction of E1 to E2β took place in sterilized soil suggesting this is not solely a biodegradation process but has abiotic transformation contribution as well.…”
Section: Metabolite Formation In E1 Treated Mesocosmsmentioning
confidence: 91%
“…However, the formation of E2β in the present study may be due to the possibility of introducing intermittent anoxic conditions in the mesocosms when adjusting their soil moisture levels during incubation. Previous studies have reported the reduction of E1 to E2β in environmental matrices such as soil columns (Goeppert et al, 2015;Du et al, 2021), suspended swine manure under anerobic conditions (Prater et al, 2015), and inoculated water under anerobic conditions (Blunt et al, 2017). In Du et al, (2021) the reduction of E1 to E2β took place in sterilized soil suggesting this is not solely a biodegradation process but has abiotic transformation contribution as well.…”
Section: Metabolite Formation In E1 Treated Mesocosmsmentioning
confidence: 91%